Flow injection chemiluminescence immunoassay based on resin beads, enzymatic amplification and a novel monoclonal antibody for determination of Hg2+. Issue 18 (21st September 2015) - Xu, Mingxia; Chen, Mengting; Dong, Tiantian; Zhao, Kang; Deng, Anping; Li, Jianguo
<x xml:space="preserve">Abstract</x> A convenient competitive immunoassay of Hg2+ using carboxylic resin beads, specific monoclonal antibody and enzymatic amplification is proposed with flow injection chemiluminescence detection.